The Studies Releated to Levonorgestrel Intrauterine_x000D_ System(Lng-Ius)-Mirena® in Turkey - UZUNER, ARZU (My University, 2020)
Levonorgestrel releasing intrauterine system (LNG-IUS) is developed as a method of contraception, due to the highprogesterone effect on the endometrium it is used for the treatment of adenomyosis, endometriosis, hyperplasia, and theirsymptoms such as menorrhagia, dysmenorrhea, and pelvic pain. It has a high contraceptive protection and low side effects. Inthis review, all the studies performed in our country about LNG-IUS were systematically investigated. A total of 36 studieswere reached, 26 were involved in the treatment area; 10 of them were related to contraceptive use. Information about the useof LNG-IUS in primary care.

Levonorgestrel salınımlı rahim içi sistem (LNG-RİS), kontrasepsiyon yöntemi olarak geliştirilmiş olup, endometriyumda etkili_x000D_ yüksek progesteron etkisi nedeniyle adenomiyozis, endometriyozis, hiperplazi gibi patolojiler ve bunların menoraji, dismenore,_x000D_ pelvik ağrı gibi semptomlarının tedavisinde de kullanılmaktadır. Kontraseptif olarak koruyuculuğu yüksek ve yan etki oranı_x000D_ oldukça düşük bulunmuştur Bu derlemede, ülkemizde yapılan LNG-RİS ile ilgili araştırmalar incelenmiştir. Toplam 36_x000D_ araştırmaya ulaşılmıştır. Bunların 26’sı tedavi alanında kullanımı ile ilgili olduğu, 10’u ise kontraseptif amaçlı kullanımı ile_x000D_ ilgili olduğu saptanmıştır. LNG-RİS’in birinci basamakta kullanımı ile ilgili çalışmaya rastlanmamıştır.
Levonorgestrelli Rahimiçi Sistem(Lng-Ris)-Mirena® İle İlgili Türkiye'de Yapılmış Çalışmalar